Usability Analysis of Aruna Heroes Enterprise Resource Planning Apps Using Heuristic Evaluation and System Usability Scale Method (A Case Study at PT Aruna Jaya Nuswantara) - Sitepu, Kris Adam Gunanta; Herdiana, Oding; Prehanto, Adi (Universitas Pendidikan Indonesia (UPI), 2024)
This study aims to evaluate the usability level of Aruna Heroes developed by PT Aruna Jaya Nuswantara. Usability is a crucial factor in assessing the success of a product in meeting user needs. Using the Heuristic Evaluation method based on the System Usability Scale, this research identifies usability issues and barriers in Aruna Heroes and provides recommendations for improvement. The research methodology used is a mixed-methods approach with a sequential explanatory design. The study combines quantitative data through the use of the SUS and qualitative data through descriptive variable analysis and interviews with Aruna Heroes users. The analysis is conducted by applying heuristic evaluation principles to the Aruna Heroes and measuring the usability level using the SUS. The research findings indicate that Aruna Heroes has achieved a good level of usability and successfully meets 9 out of 10 indicators from the Heuristic Evaluation variables. However, in the context of usability and heuristic evaluation, Aruna Heroes still has room for improvement, particularly in the areas of Help Users Recognize, Diagnose, and Recover From Errors, Error Prevention, and Help and Documentation.